GoogleTrends as a patient therapeutic education resource on extracorporeal life support: What do patients want to know?. Issue 7 (19th April 2022) - Aleman, Rene; Patel, Sinal; Frieder, Joel S.; Navia, Jose; Sheffield, Cedric; Brozzi, Nicolas A.
Abstract: Introduction: Extracorporeal membrane oxygenation (ECMO) is implemented as rescue therapy in COVID‐19 related acute distress respiratory syndrome (ARDS) and refractory hypoxemia. Google Trends (GT) is an ongoing‐developing web kit providing feedback on specific population's interests. This study uses GT to analyze the United States (US) general population interest in ECMO as COVD‐19/ARDS salvage therapy. Methods: GT was used to access data searched for the term ECMO and COVID‐19 . The gathered information included data from March 2020 to July 2021 within US territories. Search frequency, time intervals, sub‐regions, frequent topics of interest, and related searches were analyzed. Data were reported as search frequency on means, and a value of 100 represented overall peak popularity. Results: The number of Google searches related to the terms ECMO and COVID‐19 has surged and sustained interest over time ever since the initial reports of COVID‐19 in the US, from an initial mean of 34% in March 2020 to a 100% interest by April 2020, resulting in an up‐to‐date overall average of 40% interest. Over time West Virginia, Gainesville, and Houston, lead the frequency of searches in sub‐region, metro and city areas, respectively. Top search terms by frequency include: ECMO machine, COVID ECMO, what is ECMO, ECMO treatment and VV ECMO . Parallel to this, the related rising terms are: COVID ECMO, ECMO machine COVID, ECMO for COVID, ECMO machine coronavirus, and ECMO vs ventilator . Seemingly, medical‐relevant websites fail to adequately address these for patient therapeutic education (PTE) purposes. Conclusions: GT complements the understanding of interest in ECMO for COVID‐19. When properly interpreted, the use of these trends can potentially improve on PTE and therapy awareness via specific medical relevant websites.